2015
DOI: 10.1186/s40425-015-0063-3
|View full text |Cite
|
Sign up to set email alerts
|

NK cells and CD8+ T cells cooperate to improve therapeutic responses in melanoma treated with interleukin-2 (IL-2) and CTLA-4 blockade

Abstract: BackgroundMelanoma is one of the few types of cancer with an increasing annual incidence. While a number of immunotherapies for melanoma have been associated with significant clinical benefit, including high-dose IL-2 and cytotoxic T lymphocyte antigen 4 (CTLA-4) blockade, clinical response to either of these single agents has been limited to 11-20% of treated patients. Therefore, in this study, we sought to test the hypothesis that the combination of IL-2 and CTLA-4 blockade could mediate a more profound ther… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
43
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 53 publications
(45 citation statements)
references
References 51 publications
2
43
0
Order By: Relevance
“…A very recent study also showed that an anti-CTLA-4-EGFR immunoconjugate enhances the in vitro lysis of breast cancer cells by NK cells (Passariello et al, 2020). In B16 melanoma models, NK cells and CD8+ T cells synergistically clear tumors in response to anti-CTLA-4 and IL-2 treatment (Kohlhapp et al, 2015). Furthermore, anti-CTLA-4 has been shown to increase transcriptional markers of NK cell cytotoxic activity in CT26 colon carcinoma tumors (Sanseviero et al, 2019).…”
Section: Discussionmentioning
confidence: 94%
“…A very recent study also showed that an anti-CTLA-4-EGFR immunoconjugate enhances the in vitro lysis of breast cancer cells by NK cells (Passariello et al, 2020). In B16 melanoma models, NK cells and CD8+ T cells synergistically clear tumors in response to anti-CTLA-4 and IL-2 treatment (Kohlhapp et al, 2015). Furthermore, anti-CTLA-4 has been shown to increase transcriptional markers of NK cell cytotoxic activity in CT26 colon carcinoma tumors (Sanseviero et al, 2019).…”
Section: Discussionmentioning
confidence: 94%
“…In mice, efficacy of ipilimumab and IL2 in combination was dependent on both CD8 + T and NK cells. Codepletion of these subsets (but not either one alone) abrogated the therapeutic effect (38). Ipilimumab has been shown to trigger antibody dependent cellular cytotoxicity (ADCC) of CTLA-4–expressing melanoma cell lines through TNFα release by CD16 + NK cells (39) and can mediate lysis of Tregs via CD16 + nonclassical monocytes (40).…”
Section: Discussionmentioning
confidence: 99%
“…The role of NK cells in TIL products is unclear, but could prove valuable as shown in murine B16 melanoma, where the depletion of NK cells and CD8 C T cells together (but not either alone) abrogated the therapeutic efficacy of high-dose IL-2 and CTLA-4 blockade. 33 Similarly, the importance of CD4 C T cells in TIL products remains poorly understood since some patients have responded well to TIL treatments dominated by CD4 C T cells. 32 Preclinically, cotreatment with tumor-specific CD4…”
Section: Discussionmentioning
confidence: 99%